Genomic Analysis of Phylotype I Strain EP1 Reveals Substantial Divergence from Other Strains in the Ralstonia solanacearum Species Complex - Li, Peng; Wang, Dechen; Yan, Jinli; Zhou, Jianuan; Deng, Yinyue; Jiang, Zide; Cao, Bihao; He, Zifu; Zhang, Lianhui (Frontiers in Microbiology, 2016)
Ralstonia solanacearum species complex is a devastating group of phytopathogens with an unusually wide host range and broad geographical distribution. R. solanacearum isolates may differ considerably in various properties including host range and pathogenicity, but the underlying genetic bases remain vague. Here, we conducted the genome sequencing of strain EP1 isolated from Guangdong Province of China, which belongs to phylotype I and is highly virulent to a range of solanaceous crops. Its complete genome contains a 3.95-Mb chromosome and a 2.05-Mb mega-plasmid, which is considerably bigger than reported genomes of other R. solanacearum strains. Both the chromosome and the mega-plasmid have essential house-keeping genes and many virulence genes. Comparative analysis of strain EP1 with other 3 phylotype I and 3 phylotype II, III, IV strains unveiled substantial genome rearrangements, insertions and deletions. Genome sequences are relatively conserved among the 4 phylotype I strains, but more divergent among strains of different phylotypes. Moreover, the strains exhibited considerable variations in their key virulence genes, including those encoding secretion systems and type III effectors. Our results provide valuable information for further elucidation of the genetic basis of diversified virulences and host range of R. solanacearum species.